A cohesion policy analysis for Romania towards the 2021-2027 programming period - Francesca Crucitti; Nicholas-Joseph Lazarou; Philippe Monfort; Simone Salotti (European Commission, Joint Research Centre (JRC), 2022)
We present an analysis on cohesion policy investments in the regions of Romania using the spatial dynamic general equilibrium model RHOMOLO in order to provide useful insights on the 2021-2027 programmes and their implications for growth and development. The analysis is based on a hypothetical distribution of the funding across the following fields of intervention: aid to the private sector, research and development, transport infrastructure, other infrastructure, and human capital. These interventions are modelled using a mix of demand and supply side shocks. We find that a projected exteuro31.3 billion of cohesion policy funding would increase Romanian GDP by 3.8% at the end of the 10-years implementation period with respect to the no policy scenario. Our results suggest that there seems to be an equity-efficiency trade-off in Romania: in most cases, the returns of the policy in terms of GDP are maximised by investing in the capital city region, at the expense of worsening regional disparities. For some fields of intervention, though, the spillovers generated in the less developed regions are so large that the national GDP impact is similar when investing there rather than in the capital city region.
Keywords: C68; R13; 330; RHOMOLO; Cohesion Policy; regional growth; regional development; Romania